Consensus and Liberal Legitimacy: From First to Second Best? - Landes, Xavier (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2017)
In this article, consensus, defined as the consent of all citizens, is argued to be the first best for part of the liberal tradition on political legitimacy. Consensus would be the foundation of the liberal society that, when out of reach, needs to be approximated through, for instance, voting (majority rule). I build on the timid attempts in political theory at using the theorem of the second best as a tool to settle difficult decision making in applied political theory. More precisely, I defend the view that consensus would be the first best for part of the liberal tradition on political legitimacy. Furthermore, I illustrate how moral, factual, (and, incidentally, epistemological) disagreements may create second-best problems, especially in terms of stability. Finally, I spell out some reasons why such problems directly affect a liberal order, on pragmatic grounds. The final purpose is to contribute to the literatures on legitimacy and on the application of the theorem of the second best outside economics. The key idea is to stress that much more work has to be done for “importing” the theorem of the second best into political theory.